How we can Improve Students Interest in Asking and Answering Questions in the Classroom, The Case of Second Year Social Science Students of BHU in 2020 - Wodajo, Mengesha Robso; Hailu, Bayisa; Tasente, Tanase (Technium Social Sciences Journal, 2021)
This education research tries to look at student’s low interest in asking and answering questions in social science courses and teacher’s efforts, mechanisms and hard workings to improve students’ interest and participation in a class room and other project works. Likewise, the paper also assess and examine the causes of some students being silence in class room when they are addressed different individual and group class works in their session; and results that has been occur, after teachers tried to used and applied different evaluation strategies and pedagogical systems to motivate and initiate pupils to be active participant.